Out of sight. Considering water, landscape and segregation: an investigation of Bloemfontein and its peripheral communities - Stuart, Neil (My University, 2019)
The investigation aims to uncover the important relationship between water, landscape and segregation in Bloemfontein and its peripheral communities. At the core of South African settlements, the colonial impression is visible within the spatial configuration of buildings and the expression of the grid. These characteristics were used to project socio-political ideals. Landscape and the access to water guided the setting and layout of these towns. It’s only when leaving the town that the spatial significance is noticeable, with the peripheral community on the outskirts of the town. It is this introduction to the second urban core, that generated the interest towards the investigation. The mapping of this physical and symbolic inside of Bloemfontein indicates that there is a need to fill a gap in the north-east quadrant of the city and to establish significant anchors to the east of the railway, extending towards the peripheral communities of Thaba Nchu and Botshabelo. The historical and present relevance of the three themes suggests that the answer to the solution lies in sustainable development and creating equal access to the cities that are just in nature. The thesis therefore aims to present a positive view point, that the opportunity to encourage growth and prosperity in Bloemfontein is rooted in its dependency on a natural resource, water.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand. In partial fulfilment of the requirements for the degree of Mater of Urban Design. Johannesburg 2019